IMPROVING ENGLISH SPEAKING SKILL WITH LOCAL CULTURE-BASED LEARNING THROUGH BIG BOOK - Firdha Akhdania Kamilah; Fuzi Fauziyah; Vina Aini Salsabila; Milma Vinca Cantikka Hidayat (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2019)
This study aims to describe the implementation of language learning by applying local cultures through big book and to find out the improvement of students’ English speaking skill by using big book. This study applies Classroom Action Research (CAR) which had two cycles consisted of planning, action, observation, and reflection. This study involved 30 students of grade VB of Islam Kreatif Muhammadiyah Elementary School Cianjur. The data of this study were gathered from observation, questionnaire, and interview. Then, the data were analyzed by comparing the score of each cycle for the quantitative data and triangulation for the qualitative data. According to the data, the study indicates there was an improvement in cycle one to cycle two. In cycle one, the average score was 64,4 and 76,9 in the cycle two. Furthermore, the students admitted that big book was improved their local culture knowledge, but they were not conscious that their speaking abilities were improved. The students also felt excited and enjoyed the teaching learning process. Based on these results, the researchers concluded that learning language combined with local cultures by using big book gave positive impacts on improving students’ English speaking skill and students’ local cultures knowledge.